Missing persons - White, Stephen, 1951- (New York : Signet, 2005)
When his colleague dies under mysterious circumstances, psychologist Alan Gregory finds himself questioning the integrity of those closest to him, tracking an elusive patient, and looking for clues within the complex mind of a client.
Originally published: New York : Dutton, 2005.
Keywords: Gregory, Alan (Fictitious character) -- Fiction; Psychotherapist and patient -- Fiction; Paranoid schizophrenics -- Fiction; Clinical psychologists -- Fiction; Missing persons -- Fiction; Boulder (Colo.) -- Fiction; Psychological fiction; Mystery fiction